Benefits of SWOT Analysis in Marketing Strategy for Sustainable Business Management - Marissa Grace Haque; Muhammad Yasir; Robertus Suradji; Istianingsih Istianingsih (Return : Study of Management, Economic and Bussines, 2024)
By developing the right marketing strategy based on a thorough SWOT analysis, the company can improve its performance and achieve sustainable growth according to targets. Especially when business competition in the world is getting tighter, and geopolitical shifts significantly influence geoeconomics, which has an impact on the national economy. Company management needs to implement marketing strategies more vigilantly, so that they remain effective and efficient, on an ongoing basis. In this context, SWOT analysis is used as a tool to reveal strengths, weaknesses, internal opportunities as well as external threats and opportunities. SWOT analysis can help company management to develop increasingly precise marketing strategies, with the aim of increasing sales volume. The results of the research show that the use of SWOT analysis supports company management in developing more effective and efficient marketing strategies, so as to increase the sales volume of products and services in an increasingly competitive world market.